Effect of care programme based on Comfort Theory on reducing parental anxiety in the paediatric day surgery: Randomised controlled trial. Issue 7 (8th July 2021) - Pazarcikci, Fahriye; Efe, Emine
Abstract: Aims and Objectives: The aim of the study was to determine the effect of a care programme based on the Comfort Theory on reducing parental anxiety forming during the perioperative process of paediatric day surgery. Background: According to the Comfort Theory, nurses provide comfort and take precautions related to comfort, and they provide care and assistance by encouraging individuals/families/society and supporting coping methods. This study is the first randomised controlled study to test the effect of a nursing care programme based on the Comfort Theory for paediatric day surgery. Design: Randomised controlled trial. Methods: The research was completed from June–September 2019 with participation of parents whose children were undergoing paediatric day surgery at a hospital in the Mediterranean region of Turkey. A total of 120 participants were randomly assigned to two equal groups. The intervention group received care programme based on Comfort Theory. The control group received nursing care routinely provided in the clinic. Data were collected using the State‐Trait Anxiety Inventory. Measures were obtained at six points, at baseline, at four interval observations after the initial point and during follow‐up on the 10th postoperative day. The repeated measures ANOVA test and t ‐test for independent samples were used to compare the anxiety levels between the intervention and control groups. Results: There was a statistically significant difference in favour of the group receiving the care programme based on the Comfort Theory when the anxiety levels between the intervention and control groups were compared. Conclusions: The care programme based on the Comfort Theory was effective in reducing parental anxiety forming in the perioperative process of paediatric day surgery. Relevance to clinical practice: The results of this study show the applicability of the care programme for paediatric day surgery. It is recommended that this programme be introduced to nurses in paediatric day surgery.